RETRACTED: Forecasting rolling stock indicators in the market of transport services using the neural network method - Zadorozhniy Vyacheslav; Zyryankina Ksenia; Bakalov Maksim (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001